Team resilience: A scoping review of conceptual and empirical work. Issue 1 (2nd January 2020) - Chapman, Michael T.; Lines, Robin L. J.; Crane, Monique; Ducker, Kagan J.; Ntoumanis, Nikos; Peeling, Peter; Parker, Sharon K.; Quested, Eleanor; Temby, Philip; Thøgersen-Ntoumani, Cecilie; Gucciardi, Daniel F.
ABSTRACT: The purpose of this scoping review was to examine the literature on team resilience to gain insight into current thinking regarding its definition and conceptualisation, and to identify how researchers have operationalised and measured this concept. We conducted a systematic scoping review using the 5-phase approach proposed by Arksey and O'Malley. A total of seven databases were searched, followed by a citation search of eligible papers via Google Scholar. Of the 275 articles identified via the search process, 27 papers were deemed eligible for review. Several key findings regarding the literature on team resilience were observed: (i) definitions varied in terms of content (e.g. input or process), breadth (e.g. unidimensional versus multidimensional), and quality (e.g. essential and necessary attributes of key components); (ii) there was a predominance of single-level conceptualisations of team resilience; and (iii) there has been a reliance on cross-sectional research designs in empirical studies, which is incongruent with the dynamic nature of this concept. Key recommendations from this scoping review focus on definitional, theoretical, and methodological issues.